Pengaruh Walking Morning Exercise Terhadap Peningkatan Kualitas Tidur pada Lansia - Oktaviatama, Anisah; Mirawati, Dita; Setiawan, Cahyo (Jurnal Kesehatan Andalas, 2023)
Physiological and psychological problems can arise from sleep disorders. The majority of older people experience a decrease in sleep quality with age, so it is necessary to do morning physical activity such as walking to improve sleep quality. Objective: To determine whether walking in the morning exercise can improve older people's sleep quality. Methods: It was a quantitative research with a quasi-experimental type using a one-group pre and post-test design. The sample consisted of 28 respondents selected by purposive sampling. Measurement of sleep quality using the Pittsburgh Sleep Quality Index (PSQI) questionnaire to evaluate a person's sleep quality. The walking morning exercise intervention was carried out thrice a week for up to 4 weeks. Results: Wilcoxon test for bivariate analysis showed a significance level of 0.008 (p < 0.05). Conclusion: Walking in the morning exercise improves sleep quality in older people.Keywords: Â older people, sleep quality, walking morning exercise